2013
DOI: 10.1007/s12603-013-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

Blood trace minerals concentrations and oxidative stress in patients with obstructive sleep apnea

Abstract: Abnormal concentrations of these trace minerals may reflect oxidative damage and inflammatory response, thus increasing the severity of OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 40 publications
1
30
1
Order By: Relevance
“…In addition, Mn is an important antioxidant. Cobalt (Co) is a critical fragment of vitamin B 12 that is crucial in foliate and fatty acid metabolism [6] . Lead (Pb) down-regulates nitric oxide production and induces oxidative stress and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mn is an important antioxidant. Cobalt (Co) is a critical fragment of vitamin B 12 that is crucial in foliate and fatty acid metabolism [6] . Lead (Pb) down-regulates nitric oxide production and induces oxidative stress and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Infusion of selective inhibitors of PGDS, e.g., tetravalent selenium compounds, reversibly, time-and dose-dependently inhibited both nonrapid eye movement (NREM) and rapid eye movement (REM) sleep during the daytime [194], which shows that PGDS plays a crucial role in the regulation of physiological sleep. Selenium deficit may result in severe disorders [195,196], including mood disorders. Gosney et al [197] reported the effects of micronutrient supplementation on mood in nursing home residents; selenium supplementation was directly correlated with decreases in depression scores and increases in serum levels.…”
Section: Seleniummentioning
confidence: 99%
“…Development of these conditions has been attributed to increased levels of intracellular reactive oxygen species (ROS) during reoxygenation coupled [6] with reduced levels of antioxidant enzymes [7, 8]. Cardiac dysfunction in OSA is also attributed to hypoxia-associated increases in inflammation [9, 10]. High circulating levels of proinflammatory cytokines, such as tumour necrosis factor α (TNF-α), interleukin 6 (IL-6), monocyte chemoattractant protein 1 (MCP-1), and vascular cell adhesion molecule 1 (VCAM-1), have been found in OSA patients [1114].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that patients with OSA may benefit from zinc replacement therapy to decrease oxidative stress and reduce inflammation [9, 15]. Although zinc supplementation can provide protective antioxidant and anti-inflammatory effects [1618], cardiac function will decline with increasing age without the stimulus of exercise [19].…”
Section: Introductionmentioning
confidence: 99%